Employee Job Security, Emotional Stability and Adaptability in Predicting Employee Retention among Gen Z Employees - Amalia, Rifa; ., Sugeng; Deputri, Salsa Tri Wulandari; Siddiq, Dedi Muhammad; Syaroni, Bachrudin; Mustafa, Tismazammi (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study aims to discuss job security, emotional stability and adaptability in predicting employee retention of Gen Z employees in Indonesia. Design/methodology/approach: This research uses a quantitative approach with primary data collection. The sample taken was 133 respondents. The data analysis technique used is multiple linear regression using SPSS. Findings: This study found that job security, emotional stability and adaptability succeed to predict employee retention among Gen Z employees in the research context. Research limitations/implications: This study only examines the effect of predictor variables on outcome variables in the context of a manufacturing company and involves only 133 respondents. Practical implications: This finding informs managers that to increase the stay rate of Gen Z employees, their perceptions of job security, emotional stability, and adaptability are important to be maintained. Hence, management needs to pay attention and implement strategies that strengthen these factors to increase the employee retention of Gen Z employees. Originality/value: This paper is an original paper because it has not been published anywhere. Paper type: Research Paper